TATA KELOLA ORGANISASI DAN DOMINASI SOSIAL - Dien Yudithadewi; Dodo Darsono; Bonifasius Santiko Parikesit (Jurnal Akuntansi Bisnis dan Humaniora, 2023)
This study focuses on the governance of Kelompok Perempuan Kreatif Mandiri/Independent Creative Women Group (KPKM) which is the beneficiary of women's empowerment program from Corporate Social Responsibility (CSR) PT Perusahaan Gas Negara Tbk. The paper aims to identify and describe, how organizational structure impacts governance patterns and the outcomes. It used a persuasive case study approach, where the data collection process is carried out through in-depth interviews with relevant stakeholders. Likewise, researchers conducted close observation, supported with literature review from journals, digital media and books, to enrich the study. The research findings reveal that the absence of regeneration in the organizational structure causes repetitive governance pattern since its establishment, same persons are appointed as caretakers in several bodies, depending on a central figure, and only able to innovate through the intervention of outsiders (other parties). Furthermore, there is a concern regarding potential digression, as quoted from Lord Acton's letter to the Bishop of Creighton in 1887; "Power tends to corrupt and absolute power corrupts absolutely”.